Metal Coated Coir Fiber for Smart Textile Applications - U. S. Sarma (International Coconut Community, 2010)
Thermo regulated textiles attracted attention in cold countries for outdoor activities in extreme winter conditions. Temperature regulation of textiles for use in adverse environmental condition can be achieved by integrating heat regulated natural fibers into textile construction. Coir being an abundantly available, cheap and biodegradable natural fiber seems to be a material worthy of investigation. Light weight and insulation of coir fiber add to the comfort of the wearer in textile application. In this study, coir surface is made conductive by metal coating and temperature regulation is achieved by applying a small voltage. Copper, aluminium and silver metals are used for coating the coir fiber surface. Thin film coating on one side of coir fiber is done by vacuum deposition technique. Temperature regulation of upto 12 degrees is found to be possible by the application of a potential of about 1 Volt. Analysis of variance is used to compare the effect of thickness of coating and type of coating material on heat production with respect to voltage. Metal coating on coir fiber is found to provide a versatile combination of physical, thermal and optical properties and can be subjected to textile processing without any problem for the development of smart textiles.